A Truncated Waveguide Fed by a Microstrip as a Radiating Element for High-Performance Automotive Anticollision Radars - Giovanni Andrea Casula; Giuseppe Mazzarella; Giorgio Montisci (International Journal of Antennas and Propagation, 2012)
A small truncated waveguide fed by a microstrip line through a transverse coupling slot is proposed and assessed as a high-performance antenna and array element in the K band and above. This antenna allows to obtain a high radiated power, with a very low cross-polar component in the radiated field. It is therefore particularly suitable for application in automotive anticollision radars. The proposed radiating element has been analyzed by a numerical code based on an in-house method of moments, and the microstrip feeding line has been modeled by its equivalent magnetic-wall waveguide. A linear array of such elements has been designed and matched with a BPF-inspired matching network allowing an in-band behavior suitable for anti-collision radar use, with an out-of-band rejection large enough to avoid the first receiving BPF.